Process of Processing Moringa Leaves into Chocolate Moringa at PT. Mond Nature Sustainable - Tanjung, Lailatul Syifa; Silma , Muhammad; Yusmita, Yesi; Sari, Resy Kumala (Journal of Engineering Science and Technology Management, 2024)
In addition to considering food ingredients, processing techniques are one of the important factors in producing high-taste food and maintaining nutritional consistency. In Indonesia, there is a term for food processing that uses English. This study aims to analyze food processing techniques. The method used in this study is a qualitative descriptive method. The data collection technique in this study is carried out by observing individuals who work as production heads. The results of the study showed that food processing techniques included harvesting techniques, drying techniques, milling techniques, sieving techniques, chocolate making techniques and packaging techniques.